2013
DOI: 10.1002/ajpa.22463
|View full text |Cite
|
Sign up to set email alerts
|

Maternal short stature does not predict their children's fatness indicators in a nutritional dual‐burden sample of urban Mexican Maya

Abstract: 5Objective: The co-existence of very short stature due to poor chronic environment in early life 6 and obesity is becoming a public health concern in rapidly transitioning populations with high 7 levels of poverty. Individuals who have very short stature seem to be at an increased risk of poverty. These results suggest that the co-existence of very short stature and obesity appears to 24 be primarily due to exposures and experiences within a generation rather than across generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
10
2
Order By: Relevance
“…One previous study did address the hypothesis that a woman's height, as an indicator of maternal environment during her growth, exercises an intergenerational influence on child adiposity in a Maya population from Merida, Mexico (Wilson et al, ). In contrast to the present results, these authors found that short stature in Maya women did not predict their children's BMI, WC or percentage body fat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study did address the hypothesis that a woman's height, as an indicator of maternal environment during her growth, exercises an intergenerational influence on child adiposity in a Maya population from Merida, Mexico (Wilson et al, ). In contrast to the present results, these authors found that short stature in Maya women did not predict their children's BMI, WC or percentage body fat.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently low mean height values (<148 cm) have been reported for adult Maya women in Merida (Azcorra et al, ; Varela‐Silva et al, ), largely due to chronic adverse living conditions. Yucatan, particularly Merida, has also strikingly high rates of overweight and obesity among children and adults (Azcorra, Dickinson, & Rothenberg, ; Azcorra et al, ; Datta Banik, Andrade Olalde, Rodriguez, & Dickinson, ; Datta Banik, Castillo, Rodriguez, & Dickinson, ; Mendez et al, ; Varela‐Silva et al, ; Wilson et al, ). A recent National Survey of Health and Nutrition in Mexico (INSP, ) found that children 5‐ to 11‐years‐of‐age in Yucatan had a 22% risk for overweight (>+1 standard deviation or SD and ≤ +2 SD of BMI‐for‐age), and 23% for obesity (>+2 SD of BMI‐for‐age).…”
Section: Participants and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We objectively measured the physical activity of 33 of the 58 children in the FFQ sample (17 boys) over a one week period (Wilson et al, 2011(Wilson et al, , 2013. We found they were highly active, overall, spending an average of 120 min per day in moderate-to-vigorous physical activity (MVPA), which exceeds international recommendations for their age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are not isolated, as similar reports come from several other low socioeconomic status groups in both developing and developed nations . Several hypotheses have been proposed to explain the nutritional dual-burden (Frisancho 2003, Varela-Silva et al 2007, Said-Mohamed et al 2012, Wilson et al 2013. In the following analysis we examine the most basic of these hypothesesthat the diet of the Maya mothers and children participating in our studies is deficient in one or more nutrients essential for skeletal growth, but excessive in total energy.…”
Section: The Maya Of Meridamentioning
confidence: 96%